Racotumomab: an anti-idiotype vaccine related to N-glycolyl-containing gangliosides – preclinical and clinical data - Vázquez, Ana María; Hernández, Ana María; Macías, Amparo; Montero, Enrique; Gómez, Daniel E.; Alonso, Daniel F.; Gabri, Mariano R.; Gómez, Roberto (Frontiers in Oncology, 2012)
Neu-glycolyl (NeuGc) containing gangliosides are attractive targets for immunotherapy with anti-idiotype mAbs, because these glycolipids are not normal components of the cytoplasmatic membrane in humans, but their expression has been demonstrated in several human malignant tumors. Racotumomab is an anti-idiotype mAb specific to P3 mAb, an antibody which reacts to NeuGc-containing gangliosides, sulfatides and other antigens expressed in tumors. Preparations containing racotumomab were able to induce a strong antimetastatic effect in tumor-bearing mice. Different Phase I clinical trials have been conducted in patients with advanced melanoma, breast cancer and lung cancer. The results of these clinical trials demonstrated the low toxicity and the high immunogenicity of this vaccine. The induced antibodies recognized and directly killed tumor cells expressing NeuGcGM3. A Phase II/III multicenter, controlled, randomized, double blind clinical trial was conducted to evaluate the effect of aluminum hydroxide-precipitated racotumomab vaccine in overall survival in patients with advanced non-small cell lung cancer. The clinical results of this study showed a significant clinical benefit in the patients who were treated with the anti-idiotype vaccine.